Pengaruh Umur Perusahaan, Keputusan Pendanaan, Kebijakan Dividen, dan Cash Holding terhadap Nilai Perusahaan - Feisal Ahmad Riyadi (2021)
This study was conducted with the aim of knowing the effect of company age, funding decisions, dividend policy, and cash holding on firm value in manufacturing sector companies listed on the Indonesia Stock Exchange in 2015-2019. This type of research is a quantitative research using the type of data in the form of secondary data that can be obtained from the company's annual report and summary of the general meeting of shareholders (GMS). The sample that researchers use is 42 manufacturing companies. The tests that the researcher uses are classical assumption test, regression model selection test, multiple linear regression test, and partial hypothesis test (t test). The results obtained by the researchers show that (1) company age has a significant negative effect on firm value, (2) funding decisions have a significant negative effect on firm value, (3) dividend policy does not have a significant effect on firm value, and (4) cash holding has a significant negative effect on firm value.